Assessment of renal function from creatinine clearance measurement and 131I-hippuran renography in cancer patients before chemotherapy - Štabuc, Borut (Radiology and oncology (Ljubljana), 1999)
Background. Serum creatinine and endogenous creatinine clearance (CrCl) are widely used measures of renal function before prescribing nephrotoxic chemotherapy. This study compares the precision and bias in glomerular filtration rate (GFR) estimation without the need to collect urine by using Cockcroft-Gault formula on a single serum creatinine concentration (CrCo) and 131I- hippuran clearance (HC) determined from the renographic curves. Patientsand methods. Fourty-seven patients aged between 27 and 73 years were studied. In all patients, we determined serum creatinine concentration, CrCl, CrCo and HC simultaneously before treatment by combined chemotherapy with cisplatin (CDDP) and in 31 patients, before the third cycle. Serum and urine creatinine concentrations were determined with a Hitachi 911, an automated biochemical analyser CrCl was calculated from the urine flow, from the ratio between the serum and urine creatinine concentrations and was standardized forthe body surface area. Serum creatinine was used to estimate CrCo using a Cockcroft and Gault formula. HC was determined from 131I-hippuran uptake by both kidneys, results were compared to our Nuclear Medicine Department normal values with regard to the age of each patient. For the evaluation of results, Pearson's correlation coefficient and t-test with 95 % confidence interval were used. Results. The sensitivity of serum creatinine, CrCo and HC to predict CrCl<78 mL/min/1.73m2 was 41 %, 68% and 46% and specificity was 95%, 71 % and 76% respectively. Value of CoCr for prediction of reduced CrCl (sensitivity) was statistically significantly better than the HC (p=0.03). Value of CoCr fnr prediction of normal CrCl (specificity) was as good as HC (p=0.3). Conclusions. CrCl for the GFR estimation in the patients treated withnephrotoxic chemotherapy cannot be changed by CrCo and/or HC.
Keywords: Cisplatin; Creatinine; Drug therapy; Glomerular filtration rate; Iodohippuric acid; Kidney function tests; kreatinin; ledvice; Melanoma; Metabolic clearance rate; onkologija; Ovarian neoplasms; Radioisotope renography; rak (medicina); Stomach neoplasms; zdravljenje